(untitled) (Archives of Clinical Psychiatry, 2009)
These practice guidelines for the biological treatment of unipolar depressive disorders were developed by an international Task Force of the World Federation of Societies of Biological Psychiatry (WFSBP). The goal for developing these guidelines was to systematically review all available evidence pertaining to the treatment of unipolar depressive disorders, and to produce a series of practice recommendations that are clinically and scientifically meaningful based on the available evidence. These guidelines are intended for use by all physicians seeing and treating patients with these conditions. The data used for developing these guidelines have been extracted primarily from various national treatment guidelines and panels for depressive disorders, as well as from meta-analyses and reviews on the efficacy of antidepressant medications and other biological treatment interventions identified by a search of the MEDLINE database and Cochrane Library. The identified literature was evaluated with respect to the strength of evidence for its efficacy and was then categorized into four levels of evidence (A-D). This first part of the guidelines covers disease definition, classification, epidemiology and course of unipolar depressive disorders, as well as the management of the acute and continuation-phase treatment. These guidelines are primarily concerned with the biological treatment (including antidepressants, other psychopharmacological and hormonal medications, electroconvulsive therapy, light therapy, adjunctive and novel therapeutic strategies) of young adults and also, albeit to a lesser extent, children, adolescents and older adults.